COMPARISION OF ANTIDYSLIPIEMIC POTENTIAL OF 80 MILLIGRAMS OF FENOFIBRATED WITH 8 GRAMS OF NIGELLA SATIVA SEEDS DAILY - Mastoi, Shah Murad; Ali, Azmat; Aslam, Hina; Niaz, Khalid (Universal Journal of Pharmaceutical Research, 2017)
Objectives: High lipid levels in blood circulation may interact with free radicals, formed in consequence of normal metabolic processes in human body. This interaction is one of the etiological factors for development of coronary artery disease (CAD). Just to keep normal plasma lipid levels may reduce risk for CAD. To compare hypolipidemic potential of herb Nigella sativa with allopathy-related hypolipidemic agent Fenofibrate, we conducted this research. Methods: It was single blind placebo-controlled study conducted at Ghurki trust teaching hospital, Lahore from February 2017 to July 2017. 75 diagnosed secondary hyperlipidemic patients were selected with age range from 20 to 70 years. Twenty five patients of group-A were advised to take two grams of Kalonji, twice daily. All participants were advised to take these medicines for eight weeks. Serum LDL-cholesterol was calculated by Friedwald formula1 (LDL-Cholesterol= Total Cholesterol-(Triglycerides/5+HDL-Cholesterol). Data were expressed as the mean ± SD and “t” test was applied to determine statistical significance as the difference. Results: A probability value of <0.05 was considered as non-significant and P<0.001 was considered as highly significant change in the results when pre and post-treatment values were compared. Fenofibrate decreased TC, TG, and LDL-cholesterol highly significantly with p-value <0.001, while increase in HDL-cholesterol was significant with p-value <0.01. Conclusion: It was concluded from this study that hypolipidemic potential of herbal medication Nigella sativa is comparably same as hypolipidemic potential of allopathy related drug Fenofibrate when given in large amount (i.e.; 4 grams daily) for specific time. Peer Review History: Received 3 October 2017; Revised 5 November; Accepted 25 December, Available online 15 January 2018 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewer(s) detail: Dr. Hebatalla Ibrahim Ahmed Abdel Hameed , Al-Azhar University, Faculty of Pharmacy (Girls), Nasr City, Cairo, Egypt, hebatalla123@yahoo.com Dr. Masoomeh S Ghahfarokhi , University of Benin, Nigeria, mshamsgh@yahoo.com